Detecting the effects of Fabry disease in the adult human brain with diffusion tensor imaging and fast bound‐pool fraction imaging. Issue 6 (27th May 2015) - Underhill, Hunter R.; Golden‐Grant, Katie; Garrett, Lauren T.; Uhrich, Stefanie; Zielinski, Brandon A.; Scott, C. Ronald
Abstract : Background: To identify quantitative MRI parameters associated with diffusion tensor imaging (DTI) and fast bound‐pool fraction imaging (FBFI) that may detect alterations in gray matter and/or white matter in adults with Fabry disease, a lysosomal storage disorder. Materials and Methods: Twelve healthy controls (mean age ± standard deviation: 48.0 ± 12.4 years) and 10 participants with Fabry disease (46.7 ± 12.9 years) were imaged at 3.0 Tesla. Whole‐brain parametric maps of diffusion tensor metrics (apparent diffusion coefficient [ADC] and fractional anisotropy [FA]) and the bound‐pool fraction ( f ) were acquired. Mean voxel values of parametric maps from regions‐of‐interest within gray and white matter structures were compared between cases and controls using the independent t‐test. Spearman's rho was used to identify associations between parametric maps and age. Results: Compared with controls, the left thalamus of Fabry participants had an increase in FA (0.29 ± 0.02 versus 0.33 ± 0.05, respectively; P = 0.030) and a trend toward an increase in ADC (0.73 ± 00.02 versus 0.76 ± 0.03 μm 2 /s, respectively; P = 0.082). The left posterior white matter demonstrated a reduction in f (10.45 ± 0.37 versus 9.00 ± 1.84%, respectively; P = 0.035), an increase in ADC (0.78 ± 0.04 versus 0.94 ± 0.19 μm 2 /s, respectively; P = 0.024), and a trend toward a reduction in FA (0.42 ± 0.07 versus 0.36 ± 0.08, respectively; P = 0.052). Among all parameters, only f measured in the left posterior white matter was significantly associated with age in Fabry participants (rho = –0.71; P = 0.022). Conclusion: Parameters derived from DTI and FBFI detect Fabry‐related changes in the adult human brain, particularly in the posterior white matter where reductions in myelin density as measured by FBFI appear age related. J. MAGN. RESON. IMAGING 2015;42:1611–1622.